Training increases anabolic response and reduces inflammatory response to a single practice in elite male adolescent volleyball players - Nemet, D.; Portal, S.; Zadik, Z.; Pilz-Burstein, R.; Adler-Portal, D.; Meckel, Y.; Eliakim, A. (Journal of Pediatric Endocrinology and Metabolism, 2012)
We examined the effect of training on hormonal and inflammatory response to a single volleyball practice in elite adolescent players. Fourteen male, elite, national team-level, Israeli volleyball players (age, 16.3±1.1 years, Tanner stage 4-5) participated in the study. Blood samples were collected before and immediately after a typical 60-min volleyball practice, before and after 7 weeks of training during the initial phases of the volleyball season. Hormonal measurements included the anabolic hormones growth hormone (GH), insulin-like growth factor 1 (IGF-1), IGF-binding protein 3, and testosterone; the catabolic hormone cortisol; the pro-inflammatory markers interleukin (IL) 6, and the anti-inflammatory marker IL-1 receptor antagonist. Training led to a significant improvement of both anaerobic and aerobic properties. Before the training intervention, the typical volleyball practice was associated with a significant increase of GH and testosterone and also with a significant increase of IL-6. Training resulted in a significantly greater GH response (DeltaGH, 2.5±2.4 vs. 4.7±3.0 ng/mL, before and after training, respectively; p<0.02) and reduced IL-6 response (DeltaIL-6, 2.0±1.6 vs. 0.6±0.7 pg/mL, before and after training, respectively; p<0.01) to the same relative intensity volleyball practice. The results suggest that, along with the improvement of anaerobic and aerobic characteristics, training leads to a greater anabolic and reduced inflammatory response to exercise.